ANALISIS PRODUKTIVITAS MESIN TEKUK DALAM PEMBUATAN KOMPONEN FRAME CHASSIS BAK KONTAINER TRUK DENGAN METODE OVERALL EQUIPMENT EFFECTIVENESS DAN FMEA - Henderson, Theodorus; Saryatmo, M. Agung; Daywin, Frans Jusuf (Universitas Tarumanagara, 2024)
A bending machine is a machine needed to produce a container for a transport truck. In producing container tubs, PT. XYZ manufactures the necessary components in the overall formation of the body including the body frame chassis components made of steel plates. In producing truck chassis frames, it can be seen that production targets from making truck chassis frame components are not achieved in production with bending machines. This is because there is damage to components such as hydraulics, PLC, encoder and so on on the main machine, namely the bending machine. The purpose of this study is to determine the level of effectiveness and efficiency of the machine by analyzing Total Productive Maintenance with the overall equipment effectiveness method of the bending machine and the loss factor of the machine with six big losses. After that, an analysis was carried out using a fishbone diagram to find the cause of the problem from the bending machine. From the results of the study, it can be seen that the average availability value is 91.92%, the performance rate is 75.11%, the rate of quality product is 90.18%, and the overall equipment effectiveness value is 62.27%. So it can be seen that the overall equipment effectiveness value is low due to the low performance rate. The biggest percentage factor in the analysis using six big losses is reduced speed losses of 23.86%.